Optimasi Alokasi Air Daerah Irigasi Colo - Suzanti, Gemala, Dr. Mamok Suprapto, M. Eng, Ir. Jaji Abdurrosyid, MT (2015)
Water resource management in irrigated areas (DI) is highly dependent on the technical dependable/reliable discharge by a factor of K as a criterion. However, although the K-factor has been met, in some DI still occur crop failure due to lack of water. This is due to factors-K does not pay attention to the time at which the event of excess or shortage of water during the growing plants. Therefore, it is necessary to use other criteria to assess the performance of irrigation systems. This study used a yardstick form Reliability Index (Ia) and a resilience index (Ik). The best value of Ia and Ik is approaching of 1 (one). Based on the research results, the value Ia = 0.06 and Ik = 0.18 (MT 1) and Ia = 0.42 and Ik = 0.29 (MT 2) to DI Colo West maximum achievable if RTTG begins on 15 September. While DI East Colo, Ia = 0:06 and Ik = 0:18 (MT 1) and Ia = 0.38 and Ik = 0:13 (MT 2) The maximum achievable if RTTG begins on 1 October. Benchmarks based on the value he and Ik is still relatively low for two DI, whereas the K-factor contained in RTTG including either category, namely the K-factor = 75% for DI East Colo and K factor = 71% for DI Col West. Based on the results of the study showed that the field condition more in line with the benchmarks Ia and Ik compared with K-factor. This is evident because in the two of DI frequent crop failure due to lack of water. It is advisable to use the benchmarks Ia and Ik in management for DI East Colo and West Colo, to ensure the growth and success of the production plant.